An Overview of the Key Theories of Foreign Direct Investment: The Way Forward - Marandu, Edward Elirehema; Ditshweu, Tebo (Advances in Social Sciences Research Journal, 2018)
This paper discusses eight of the numerous theories that seek to explain why and when foreign direct investment takes place. In addition, general criteria for a good theory were provided as suggested. The main finding is that there is no single, generally accepted theory that currently satisfies all the listed criteria for a good theory or gives a satisfactory explanation about the determinants of FDI. The paper argues that a good theory of FDI should be able to explain simultaneously exporting as well as portfolio and foreign direct investments for these are basically similar activities that reflect a continuum of increasing level of involvement of the firm in international operations. The authors advise that a good starting point in developing a theory of FDI the theory of economic advantage which is static and more applicable to natural advantages such as minerals and agriculture. On the other hand, the Product Life Cycle Theory is dynamic and suggests that comparative advantage shifts from one nation to another as a product matures. Therefore, the PLC may be a good starting point in developing a theory of FDI flows associated with products that depend mainly on acquired advantages such as manufactured goods. The PLC may therefore be seen as taking over where the classical comparative advantage theory fails to explain trade and investment.